Hearing in fishes and reptiles - S, Kameswaran; PV, Rajender Kumar (Journal of All India Institute of Speech and Hearing)
Very little work has been done on trie hearing capacity or mechanism of the lower vertebrates in India. Several experimenters such as Kreidl (1895) concluded that fishes were deaf or, at best, could receive some vibrations through cutaneous sense. Only after Bigelow (1904) and others, it was proved conclusively that fishes do perceive sound. In this study an attempt is made to evaluate the hearing capacity of a few fishes and reptiles of South India